QUALITY CONTROL OF GC PERFORMANCE FOR STEROID ANALYSIS - Iryanti Eka Suprihatin (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2011)
This paper reports the process conducted to maintain a high quality of GC responses in obtaining reliabledata on steroid analyses of environmental samples. Works including setting up the Limit of Detection (LOD) andLimit of Quantitation (LOQ), maintaining linearity, controlling the reproducibility, and determining its reliability aredescribed. It is evident that in this work the LOD of the GC is 0.0002 ng (by 1 mL injection of 0.2 mgL-1 samples) andthe LOQ is 0.001 ng (by 1 mL injection of 1 mgL-1 samples), which means it is capable of detecting much lowerconcentrations of steroid compounds if the samples undergo 2000 times pre-concentration during preparation. Underthe range investigated the GC provides reliable quantitative linear responses to all steroid compounds.